STUDY OF SORPTION PROPERTIES OF OXIDIZED SORBENTS OBTAINED FROM DOGWOOD SEEDS (Proceedings of the YSU B: Chemical and Biological Sciences, 2024)
The results of studying the sorption properties of bifunctional carbon sorbents obtained from dogwood seed shells are presented. It is shown that the greatest content of surface oxygen-containing groups is provided by oxidation of carbonizates by hydrogen peroxide generated in an electrochemical cell. The optimal oxidation mode was the use of 5 M sulfuric acid solution as an electrolyte, and the current density was 15 mA/cm2. The sorption of Fe2+, Cu2+, Ni2+, Sn2+, Al3+, Mg2+, Ca2+ ions was studied under static conditions at pH 1.5–6.0. It is shown that the highest degree of extraction of these ions is observed at pH 4.5–5.0. The optimal conditions of extraction of the ions, distribution coefficients and static sorption capacities are presented. According to the distribution coefficients, the indicated ions are distributed as follows: Fe2+ > Cu2+ > Ni2+ > Sn2+ > Al3+ > Mg2+ > Ca2+.
Keywords: bifunctional sorbents; enterosorption; oxidized coals; sorption of heavy metals